Economic reintegration of returning overseas Filipino workers - dela Cruz, Nicole Ann M. (College of Home Economics, University of the Philippines Diliman, 2019)
This study investigated how returning OFWs economically reintegrated in terms of employment, investment, and other entrepreneurial activities. This study also looked into how the economic situations changed throughout the employment timeline: before, during, and after working abroad. Lastly, this study described the family financial management of returning OFWs in preparation of their overseas employment as well as their preparation upon return. A total of 14 respondents were interviewed by the researcher, eleven of which are returning OFWs with teaching-related professions (TRPs), and the remaining three are with non teaching-related professions (NTRPs). Frequency distribution and content analysis selective coding were used to analyze and present qualitative data from the respondents. The results of this study revealed that returning OFWs had a smooth reintegration and prioritize employment as a way to economically reintegrate rather than participating in investment or entrepreneurial activities. Returning OFWs generally plan with their families regarding family matters and some financial aspect. Generally, the economic reintegration was described by the returning OFWs as easy and fast. Working abroad has positive gains on OFWs and their families but there must be serious efforts in encouraging their return. However, there are also risks that returning OFWs must consider in preparation for overseas employment and even upon return. The risk of knowledge and work mismatch, economic status downgrade, and debt acquisition. Thus, proper planning and household resource management must be strengthened in order to resolve such risks.